Enhancing emotional health and engagement in Chinese English language learners: an approach from teachers’ autonomy- supportive behavior, teachers’ harmony, and peer support in a two-sample study - Yang, Liu (Frontiers in Psychology, 2024)
In the evolving landscape of Chinese education, understanding the factors that influence the emotional health and engagement of English language learners is increasingly vital. This study investigates the roles of Teachers' autonomy-supportive behavior, teachers' harmony, and peer support in influencing the emotional health and engagement of English language learners in China. This research also explored the mediating role of Peers' support and Teachers' harmony into the relationships between Teachers' autonomy-supportive behavior and their outcomes.Involving two samples of 68 English Language Teachers and their 389 students from various Chinese universities, the study leverages a convenience sampling method. Key findings indicate that students' engagement is significantly affected by a combination of teachers' autonomysupportive behavior, peer support, and teachers' harmony; while students' emotional health is predominantly influenced by peer support. These outcomes highlight the importance of both teacher behavior and peer relationships in educational settings, underscoring their crucial roles in enhancing student well-being and engagement. The study's methodology, incorporating two samples, teachers and their students, from multiple educational institutions and a comprehensive analytical approach, offers robust insights. The indirect effects through Teachers' harmony and teachers' harmony and Peers' support showed statistical significance. The present findings are highly relevant to promote interventions for teachers' professional development communities, that help them in improving psychological harmony and further impact on desirable students' outcomes. Despite that the limitations due to convenience sampling and self-report measures, the study provides empirical findings on the mediating role of Teachers' harmony and Peers' support into the relationships between Teachers' autonomy-supportive behavior and students' outcomes that could inform interventions for educators and learners.